Mengkritisi Fenomena Korupsi di Parlemen - Artidjo Alkostar (Jurnal Hukum IUS QUIA IUSTUM, 2008)
Corruption eradication requires not mere technological hardware and good legal enforcement institutions, but this again, requires software instrument in the form of legal culture, which encompasses the ideology of law and the ideology which legal apparatus adopt. More importantly, in this globalization era, corruption prevention interconnects with politics, economics, culture, law, and international world. Two elements, namely social-political control, as well as penalization which is derived from the ideal concept of justice, are key elements in this regard.